Loss of the Acetyltransferase NAA50 Induces Endoplasmic Reticulum Stress and Immune Responses and Suppresses Growth . Issue 4 (26th May 2020) - Neubauer, Matthew; Innes, Roger W.
Abstract : Knockout of the broadly conserved N-terminal acetyltransferase NAA50 in Arabidopsis thaliana induces endoplasmic reticulum stress, leading to severe dwarfism and induction of defense responses. Abstract: Stress signaling in plants is carefully regulated to ensure proper development and reproductive fitness. Overactive defense signaling can result in dwarfism as well as developmental defects. In addition to requiring a substantial amount of energy, plant stress responses place a burden upon the cellular machinery, which can result in the accumulation of misfolded proteins and endoplasmic reticulum (ER) stress. Negative regulators of stress signaling, such as ENHANCED DISEASE RESISTANCE 1 ( EDR1 ), ensure that stress responses are properly suspended when they are not needed, thereby conserving energy for growth and development. Here, we describe the role of an uncharacterized N-terminal acetyltransferase, NAA50, in the regulation of plant development and stress responses in Arabidopsis ( Arabidopsis thaliana ). Our results demonstrate that NAA50, an interactor of EDR1, plays an important role in regulating the tradeoff between plant growth and defense. Plants lacking NAA50 display severe developmental defects as well as induced stress responses. Reduction of NAA50 expression results in arrested stem and root growth as well as senescence. Furthermore, our results demonstrate that the loss of NAA50 results in constitutive ER stress signaling, indicating that NAA50 may be required for the suppression of ER stress. This work establishes NAA50 as essential for plant development and the suppression of stress responses, potentially through the regulation of ER stress.